MENJADI INDONESIA: MENCARI IDENTITAS NASIONAL - Ninawati Ninawati; Kurnia Setiawan (PROSIDING SERINA, 2021)
Every individual has an identity, Inaç and Unal (2013) say there are two types of identity, namely granted identity (given identity) and gain identity (acquired identity). The ethnic Chinese national identity is often doubted, for that from the three studies carried out related to national identity are presented through the dissemination of the research results. The purpose of this activity is to present the results of research with the theme of national identity, which at the same time is used to make posters that are contested. The dissemination was carried out through an online webinar on November 29, 2021 with 75 participants. The resource persons involved three people from the INTI association, researchers, and FSRD lecturers who organized the poster competition. The poster competition was attended by around 100 people who produced 23 posters and three winners were determined. Meanwhile, from the exposure of the research results obtained results that need to be observed, namely identity is formed depending on the environment including the narrative it receives. The discrimination narratives are still felt by the ethnic Chinese. Ethnic diversity in Indonesia, including the Chinese ethnicity. One form of diversity is acculturation, the form of integration – which is accepting Indonesian culture while still loving Chinese culture – is preferred. Knowledge and perception of national identity can be expressed in various forms, including culture, introduction to places and culinary, this meaning is contained in the posters made by the students participating in the competition. The output target obtained is an understanding of national identity that can be expressed through various media.